Karakteristik Anak Jalanan dan Bentuk-Bentuk Kekerasan terhadap Anak Jalanan di Kota Padang Provinsi Sumatera Barat - Erwin Erwin (Antropologi Indonesia, 2013)
Protection issues of children's rights in Indonesia has not received sufficient attention. Law4 of 1979 concerning child welfare, and No. 23 of 2002 on the protection of children. Children'srights, such as the right to life, the right to protection from the threats to her own safety, the right to equality in education, employment, health, the right to employment, the right to meet the needs of food, clothing and shelter. Quantitatively, the number of street children in the city of Padang in the last ten years has increased. This research provides in-depth information about the various forms of violence experienced by street children in the city of Padang. This study was conducted in five point activity gathering place and street children in the city of Padang.The study found that violence to street children and some factors which it caused the violence.Demoralization among street children is a reaction to a situation that is very limited and therigors of life on the streets. It is difficult to make strict limits on the morality of the group of street children. All forms of violence experienced by children and street, is a phenomenological reality for street children and a variety of social interactions that occur among street children in it loaded with a cargo of reciprocity, and can be seen as a form of social safety networks.Keywords: Street children, violence and abuse, social protection